Implementasi Pembelajaran Daring di Masa New Normal Pada Mata Pelajaran Fikih Kelas XI di Madrasah Aliyah Darussalamah Baruh Sampang Madura - Wulandari, Inayah Maulidiya; Lilawati, Emi (Universitas KH. A. Wahab Hasbullah, 2022)
MA Darussalamah Baruh Sampang is one of the institutions whose learning process is also affected by the Covid-19 virus pandemic. In the new-normal era, the education sector has started teaching and learning activities through online learning. Departing from these problems, the purpose of this study is to describe the implementation process, the constraints, and the impact of online learning during the new normal in fiqh subjects for class XI. This research is a qualitative research with descriptive procedure. The subjects of this study were the head of the madrasa, a fiqh teacher for class XI and one of the students of MA Darussalamah. The object of this research is the implementation of online learning in the new-normal period in class XI fiqh subjects at MA Darussalamah. Data collection techniques with the methods of observation, interviews, and documentation. The results of this study indicate that: 1) The implementation of online learning through E-learning and Whatsapp. The teacher gives assignments or fiqh material in the hope that students can apply it in everyday life. 2) Obstacles in online learning in Jurisprudence subjects are the inability of educators to explain or convey to students and students do not understand what the teacher explains and especially the signals. 3) The impact of online learning in the new-normal period is too monotonous explanations that make students bored. And more spending to buy quota.